2022
DOI: 10.1097/iop.0000000000002299
|View full text |Cite
|
Sign up to set email alerts
|

The Scleral Cap Technique for Porous and Nonporous Orbital Implants

Abstract: Purpose:To describe the results and potential benefit of a banked homologous donor scleral cap over the anterior surface of polyglactin 910 mesh-wrapped porous and nonporous orbital implants during enucleation and secondary orbital implant surgery.Methods: This is a single center, retrospective, clinical case series of 83 patients who received a polyglactin 910 mesh (Vicryl knitted mesh, undyed, Ethicon, Sommerville, New Jersey, USA) wrapped bioceramic or polymethylmethacrylate orbital implant (sphere or mound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…[4][5][6] Many techniques for secondary ball implantation have been described. These include trans-conjunctival 11,[13][14][15][16][17] or lateral brow approaches, 18 and also several ways to localize and handle the muscles. 2,3,11,[13][14][15][16][17] Most reports do not differentiate between secondary ball implantation (i.e., placement in a socket without a ball) and implant exchange, but we believe that (even if misplaced) a preexisting ball implant helps orientate a surgeon during secondary surgery, and facilitates preparation of the deeper socket tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Many techniques for secondary ball implantation have been described. These include trans-conjunctival 11,[13][14][15][16][17] or lateral brow approaches, 18 and also several ways to localize and handle the muscles. 2,3,11,[13][14][15][16][17] Most reports do not differentiate between secondary ball implantation (i.e., placement in a socket without a ball) and implant exchange, but we believe that (even if misplaced) a preexisting ball implant helps orientate a surgeon during secondary surgery, and facilitates preparation of the deeper socket tissues.…”
Section: Discussionmentioning
confidence: 99%
“…2 A very similar technique, but dividing the scleral remnant into 4, has also been described. 13 With the exception of young children and developmentally small orbits, a 20-22 mm diameter ball is our preferred size for adequate volume replacement, but an implant sizer is used where there is any doubt about the ability to close surface tissues without tension. In all cases it is imperative to insert the implant through a sterile glide (readily fashioned from the thumb of a sterile polythene glove; Fig.…”
Section: Fig 1 Usual Technique For Secondary Implantation Of An Intra...mentioning
confidence: 99%
“…24,26 Jordon et al also found no difference in donor scleral caps preventing implant exposure. 27 Previously, surgeons wrapped porous implants to ease insertion into the orbit, smooth the anterior surface, and shield the conjunctiva from erosion and underlying inflammation in order to prevent exposure. 28,29 In a survey done in 2003, more than half of ASOPRS surgeons did not wrap their orbital implants after the twentieth century.…”
Section: Discussionmentioning
confidence: 99%